DESIGN OF COMPACT BANDPASS QUASI-ELLIPTIC MICROSTRIP FILTERS - Roman E. Semernya; Sergey L. Chernyshev; Artem R. Vilenskiy; Eduard O. Mozharov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
This paper considers an algorithm for development of the sixth order compact microstrip bandpass filters with quasi-elliptic characteristics. The proposed technique is applied for synthesis of two filters for the L- and X-band. The recursive computational approach is employed to obtain the coupling matrix with simple topological implementation. Next, the full-wave transmission line analysis based on spectral-domain method of moments is applied for calculation of coupled microstrip resonator eigen frequencies. This approach is then used to compute magnitude and sign of the coupling coefficient for basic coupled resonator configurations. Finally, two quasi-elliptic filter topologies are synthesized and structure optimization in Ansys HFSS is performed. As a result, prototypes of the developed microstrip filters are manufactured and measured.